ALGORITMA UNTUK MENGKONSTRUKSI SUPER MATRIK SIMETRI FUZZY PERSEGI - Hendra Kartika (Universitas Jenderal Soedirman, 2016)
The aim of this paper is to study the super matrix fuzzy using square symmetric properties of the matrix approach. Super fuzzy symmetry square matrix is constructed using the algorithm proposed by the author. The algorithm is derived from the concept of four square fuzzy submatrices. After that, the algorithm is translated into Matlab and repeatedly studied so that it meets super matrix symmetry properties. In this algorithm, Matlab is used to support the construction of super square fuzzy symmetry matrix with a very large order.